Optical properties of surfaces - Bedeaux, Dick (Imperial College Press, 2004)
This invaluable book represents a substantial body of work describing the theory of the optical properties of thin island films and rough surfaces. In both cases the feature sizes are small compared to the wavelength of light. The approach is extremely rigorous and theoretically very thorough. The reflection, transmission and absorption of light are described. Computer programs that provide exact solutions for theoretical properties of thin island films are available, and this makes the book of great practical use. The early chapters present a comprehensive theoretical framework. In this new edition a chapter on reflection from gyrotropic media has been added. Contributions due to the gyrotropic nature of the interfacial layer are discussed.